Metabolic syndrome – time for a critical view - Gumprecht, Janusz (Przewodnik Lekarza/Guide for GPs, 2006)
The term metabolic syndrome refers to specific cardiovascular risk factors whose underlying pathophysiology is thought to be related to insulin resistance. Insulin resistance is also found to be a key feature of type 2 diabetes as well as hypertension, dyslipidemia and hemostatic disturbances. In this review an effort is made to critically evaluate the concept of the metabolic syndrome especially as a means to identify patients at elevated risk of cardiovascular diseases.